Beyond the state of life of languages… Elements for the sociolinguistic diagnosis of the interactive-linguistic dynamic of Mapuzugun/Spanish contact (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
In this paper we discuss some useful concepts to explain the opposing and complementary relationship between languages that share a specific geosociocultural context. This dynamic relationship is known as linguistic and social interactions. This paper discuss the dynamic processes arising between the mapuzugun and Spanish language, and it also explores some sociolinguistic descriptions about the Mapuche language which are mostly narrow and focus on the asymmetric relationship between languages and the results of these relationships. In this context we propose a new in situ revision of the linguistic interaction to generate territorial diagnostics that consider interactive processes, dynamic and historical, dialectical and identitary concerns that both Spanish and Mapuzugun have in the communities.
Keywords: linguistic and social interactions; languages states; language contact; bilingualism